Access to discourse, marginalisation and exclusion in conservation-induced resettlement: the case of the displaced Baka of East Cameroon. Issue 2 (3rd March 2016) - Awuh, Harrison Esam
Abstract : This paper concerns the links between discourse and the marginalization and exclusion of the Baka people living in the Dja Reserve in East Cameron. The findings reveal how various factors mediate the experience of marginalisation and exclusion after displacement and resettlements. Central to these factors is the concept of 'access' – access to the dominant discourse. The paper deconstructs the concept of access into 'potential' and 'realised' access. It also shows how 'potential' access to dominant discourse can influence 'realised' access to resources in newly resettled communities.